High-Pressure Behavior of Ca 2 SnO 4 , Sr 2 SnO 4 , and Zn 2 SnO 4 - Anzellini, Simone (2024)
The pressure-induced structural evolution of Ca2SnO4, Sr2SnO4, and Zn2SnO4 has been characterized by powder X-ray diffraction up to 20 GPa using the ALBA synchrotron radiation source and density functional theory calculations. No phase transition was observed in Ca2SnO4 and Zn2SnO4 in the investigated pressure range. The observation in Zn2SnO4 solves contradictions existing in the literature. In contrast, a phase transition was observed in Sr2SnO4 at a pressure of 9.09 GPa. The transition was characterized as from the ambient-condition tetragonal polymorph (space group I4/mmm) to the low-temperature tetragonal polymorph (space group P42/ncm). The linear compressibility of crystallographic axes and room-temperature pressure-volume equation of state are reported for the three compounds studied. Calculated elastic constants and moduli are also reported as well as a systematic discussion of the high-pressure behavior and bulk modulus of M2SnO4 stannates.